2013
DOI: 10.1371/journal.pone.0057094
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Nanoconjugated Hormone Nanoparticles for Sustained Surge of Gonadotropins and Enhanced Reproductive Output in Female Fish

Abstract: A controlled release delivery system helps to overcome the problem of short life of the leutinizing hormone releasing hormone (LHRH) in blood and avoids use of multiple injections to enhance reproductive efficacy. Chitosan- and chitosan-gold nanoconjugates of salmon LHRH of desired size, dispersity and zeta potential were synthesized and evaluated at half the dose rate against full dose of bare LHRH for their reproductive efficacy in the female fish, Cyprinus carpio. Whereas injections of both the nanoconjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 34 publications
3
43
0
3
Order By: Relevance
“…Dudhani & Kosaraju (2010) reported that formation of catechin chitosan nanoparticle at pH 5.5 resulted particle size as 130±5 nm. Rather et al (2013) said that particle size of chitosan nanoparticle of Luteinizing Hormone Releasing Hormone (LHRH) at pH 6.5 was 114±10.3 nm with PDI score 0.335. In contrast with Zengshuan et al (2002) who reported that formation of chitosan nanoparticle of insulin hormone at pH 5.3 resulting particle size by 243-271 nm with 0.50-0.57 of PDI score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dudhani & Kosaraju (2010) reported that formation of catechin chitosan nanoparticle at pH 5.5 resulted particle size as 130±5 nm. Rather et al (2013) said that particle size of chitosan nanoparticle of Luteinizing Hormone Releasing Hormone (LHRH) at pH 6.5 was 114±10.3 nm with PDI score 0.335. In contrast with Zengshuan et al (2002) who reported that formation of chitosan nanoparticle of insulin hormone at pH 5.3 resulting particle size by 243-271 nm with 0.50-0.57 of PDI score.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2008) reported that chitosan nanoparticle of estradiol hormone prepared by ionic glass method had zeta potential score and entrapment efficiency by +25.4 mV and 67% respectively. While, Rather et al (2013) said that chitosan nanoparticle of Luetinizing hormone releasing hormone (LHRH), with same method resulted zeta potention score and entrapment efficiency by -33.14±6.67 mV and 69% respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan nanoparticles (CSNPs) were prepared via ionotropic gelation of chitosan with TPP, according to a traditional method described earlier by Rather et al, 30 . Briefly, chitosan (25 mg) was dissolved in 500 mL of 0.05% acetic acid to obtain a 0.005% (w/v) chitosan solution (pH 5.5 ± 0.1).…”
Section: Methodsmentioning
confidence: 99%
“…These adverse effects are related to nanoparticle composition, surface modification, dose, exposure route and animal species [7][8][9]. In addition, emergent studies are available, regarding application of nanoparticles in reproductive technologies for inducing oocyte maturation, improving the survival and development of oocytes after cryopreservation, gene knockdown in oocytes, delivering antibodies into oocytes, sustained surge of T gonadotropins and enhanced reproductive output, and nanoparticle-based semen purification [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%